Disrupted Modulation of Alpha and Low Beta Oscillations Mediates Temporal Sequence Memory Deficits in People With Schizophrenia - Zheng, Yicong; Liu, Xiaonan L.; Hsieh, Liang-Tien; Hurtado, Mitzi; Wang, Yan; Niendam, Tara A.; Carter, Cameron S.; Ranganath, Charan; Ragland, J. Daniel (Biological psychiatry : cognitive neuroscience and neuroimaging, 2021)
People with schizophrenia (SZ) exhibit impaired episodic memory when relating objects to each other in time and space. Empirical studies and computational models suggest that low-frequency neural oscillations may be a mechanism by which the brain keeps track of temporal relationships during encoding and retrieval, with modulation of oscillatory power as sequences are learned. It is unclear whether sequence memory deficits in SZ are associated with altered neural oscillations. Using electroencephalography, this study examined neural oscillations in 51 healthy control subjects and 37 people with SZ during a temporal sequence learning task. Multiple 5-object picture sequences were presented across 4 study-test blocks in either fixed or random order. Participants answered semantic questions for each object (e.g., living/nonliving), and sequence memory was operationalized as faster responses for fixed versus random sequences. Differences in oscillatory power between fixed versus random sequences provided a neural index of temporal sequence memory. Although both groups showed reaction time differences in late blocks (blocks 3 and 4), this evidence of sequence memory was reduced in people with SZ relative to healthy control subjects. Decreases in globally distributed prestimulus alpha (8–12 Hz) and beta 1 (13–20 Hz) power for fixed versus random sequences in late blocks were also attenuated in people with SZ relative to healthy control subjects. Moreover, changes in oscillatory power predicted individual reaction time differences and fully mediated the relationship between group and sequence memory. Disrupted modulation of alpha and beta 1 electroencephalography oscillations is a candidate mechanism of temporal sequence memory deficits in people with SZ.